An Exploration of Differential State Responses to Changes in Fiscal Conditions. (15th December 2016) - Buschman, Robert D.; Sjoquist, David L.
Abstract : This paper explores legislative tax changes adopted by states in the face of exogenous budget gaps (projected deficits or surpluses) over the period 1999–2011. Our conceptual framework is based on the premise that states will respond differently to temporary budget changes than to permanent changes. The framework suggests four sets of explanatory factors beyond the size of the budget gap in explaining legislative tax changes, namely the other fiscal options for addressing the gap, the nature of political party control of state government, budgetary institutions, and socio‐economic characteristics of the state. We find supportive evidence of our hypotheses that legislative tax changes are affected by a state's budget gap, reserves, debt, unified political control, and super majority rules for tax increases, but not by balanced budget rules or changes in expenditures.